2018
DOI: 10.22146/jpti.25469
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Characterization of Rhizoctonia solani Isolates from Two Different Rice Varieties

Abstract: Six isolates of Rhizoctonia solani, i.e. two isolates collected from infected rice plants and four isolates from laboratory collection were studied by using morphological characters and molecular analysis. Un-weighted pair group method with arithmetic mean dendogram constructed based on cluster analysis showed that these isolates were grouped into three clusters at the 0.77 similarity coefficient. Cluster I consisted of BA, BNJ, and NBR isolates with 100% similarity and indicated that those were from AG 1 IA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Sclerotia growth pattern was determined to differ from isolate to isolate, independent of the collection site. Bintang et al (2017) also found similar results and states that sclerotia growth pattern may vary and is often independent of the collection area of the isolate.…”
Section: Discussionsupporting
confidence: 70%
“…Sclerotia growth pattern was determined to differ from isolate to isolate, independent of the collection site. Bintang et al (2017) also found similar results and states that sclerotia growth pattern may vary and is often independent of the collection area of the isolate.…”
Section: Discussionsupporting
confidence: 70%
“…CTAB method was used to isolate the fungal DNA. The ITS 1 and ITS 4 primers (Toda et al, 1999;Pascual et al, 2000;Priyatmojo et al, 2001, Toda et al, 2004Bintang et al, 2017) were used to amplify the ITS rDNA region. The following primers were also used to detect the specific subgroup of R. solani: Rs1F-Rs2R for R. solani AG1-IA (Sayler & Yang, 2007), AG2sp-5,8SKhotR for R. solani AG2, and AG22sp2-5,8SKhotR for R. solani AG2-2IIIB (Salazar et al, 2000, Fredricks et al, 2010.…”
Section: Molecular Identificationmentioning
confidence: 99%
“…Group AG1 has subgroup AG1-IA, which is the most important group of pathogens causing sheath blight, banded leaf, aerial blight, and brown patch in more than 27 families of dicots and monocots (Singh et al, 2016). R. solani can be identified through morphological observation (Kumar et al, 2008;Lal & Kandhari, 2009;Moni et al, 2016), ITS rDNA sequencing (Toda et al, 1999;Pascual et al, 2000;Priyatmojo et al, 2001, Toda et al, 2004Bintang et al, 2017), or specific primers for various subgroups (Salazar et al, 2000;Sayler & Yang, 2007;Fredricks et al, 2010). Rice sheath blight is caused by R. solani and two other Rhizoctonia viz.…”
Section: Introductionmentioning
confidence: 99%
“…The infected leaf sheath (5 mm 2 ) and sclerotia of the fungus from each infected sample were clean in sterilize distilled water and surface sterilized in 0.5% sodium hypochlorite solution for 30-60s, washed three times with sterilized distilled water, dried on filter paper and placed on potato dextrose agar (PDA) medium (OXOID, made in the United Kingdom) The plate was at 27-30 o C for 2-3 days incubated (Lal et al 2014;Singh et al 2018). Pure cultures were obtained by re-culture from hyphal tips and maintained on PDA (Priyatmojo et al 2001;Bintang et al 2017). Mycelial discs (Ø 5 mm) of 5-d-old cultures of each isolate were transferred to PDA and incubated for four weeks at 30 ± 2 °C (Singh et al 2014).…”
Section: Isolation Of R Solanimentioning
confidence: 99%